The Buddha and the baby : psychotherapy and meditation in working with children and adults - Monzo, Maria Pozzi (Karnac Books, 2014)
These dialogues with child, adolescent and adult psychotherapists and child psychiatrists focus on their personal as well as professional experiences. All the contributors have a long-standing practice of Buddhism or other forms of meditation. The relevance of this to their clinical work with infants, children, adolescents, families and adults is described. Buddhist principles such as suffering, impermanence, non-attachment, no-self and the Four Noble Truths influence the contributors' practice of psychotherapy with children and with the child in the adult. Similarities and differences between the two traditions of Buddhism and psychotherapy are highlighted in these dialogues, which are embedded in deep, personal and transforming experiences that are shared by the authors.